Pengaruh Model Pembelajaran Picture And Picture Terhadap Hasil Belajar Kognitif Siswa Pada Subtema 3 Memelihara Kesehatan Organ Pernapasan Manusia Kelas V Sd Negeri 097320 Serapuh - Al Yurfa Irzami; Rio Parsaoran Napitupulu; Theresia Monika Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research is experimental research, the aim of this research is to determine the effect of the Picture and Picture learning model on student learning outcomes for subtheme 3 maintaining the health of human respiratory organs in class V of SD Negeri 097320 Serapuh. The design used in this research is One-Group-Pretest-Posttest. The population used in this research was all class V students, totaling 28 students. The instruments used in this research were a pretest and posttest, each consisting of 20 multiple choice questions with the same type of questions. The data obtained during the research was then analyzed using validity tests, reliability tests, level of difficulty of questions, distinguishing power of questions, normality tests and t tests. Based on the analysis that has been carried out in this research, the research results or findings in this research are that there is an influence of the Picture and Picture learning model on student learning outcomes in sub-theme 3 how to maintain human respiratory organs in class V of SD Negeri 097320 Serapuh as proven by the results of the t test with tcount (18,710).